The use of Dynavision in sport and exercise research: A review - Ong, N. C. (International Journal of Sport and Exercise Psychology, 2020)
This paper provides a comprehensive review of existing literature relating to the use of the Dynavision in sport and exercise research. A comprehensive search of major databases such as SPORTDiscus, PsycINFO, and Google Scholar yielded 23 studies related to the topic of interest. The results showed that the Dynavision was used as a training device to improve certain abilities in participants. It was also used in concussion-related research as a tool to reduce incidence of concussion, post-concussion symptom severity, as well as to assess the occurrence of concussion in individuals. Finally, the Dynavision was used as an assessment tool to examine the effects of certain factors on visuomotor performance. The factors investigated included nutrition, exercise, sport equipment, and athlete characteristics. However, despite the potential of the Dynavision as a training and research tool in sport and exercise, there still exist certain limitations and problems in current literature that need to be addressed in future research. Lastly, future applications using the Dynavision in sport and exercise research were also considered and discussed.